2021
DOI: 10.17957/ijab/15.1646
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Fiber Related Gbwri1 Complements Seed Phenotype in Arabidopsis thaliana

Abstract: WRINKLED1 belongs to AP2/EREB family of transcription factors whose role has been well established in seed oil biosynthesis. The objective of the study was to trace the role of fiber related Gbwri1 in seed development and fatty acid biosynthesis. In this study, we isolated a transcript from elite fiber producing cotton (Gossypium barbadense), which is over-expressed in G. barbadense fibers as compared to G. hirsutum and G. arboreum. The putative protein encoded by this transcript exhibited homology in specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…In our previous studies, the expression of wrinked-1, an ethylene responsive transcription factor showed highest expression in fibers of G. barbadense as compared to G. hirsutum and G. arboreum 15 . Transformation studies of Gbwri1 (EREB) in Arabidopsis thaliana have also demonstrated its role in fiber development 28 . The highest expression of this ethylene responsive transcription factor might also play a supportive tool in exploring the role of ethylene in fiber development.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, the expression of wrinked-1, an ethylene responsive transcription factor showed highest expression in fibers of G. barbadense as compared to G. hirsutum and G. arboreum 15 . Transformation studies of Gbwri1 (EREB) in Arabidopsis thaliana have also demonstrated its role in fiber development 28 . The highest expression of this ethylene responsive transcription factor might also play a supportive tool in exploring the role of ethylene in fiber development.…”
Section: Discussionmentioning
confidence: 99%